1998
DOI: 10.1097/00007632-199812010-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compressive Force Applied to the Intervertebral Disc in Vivo

Abstract: A high compressive force applied to the disc over a period of time initiates changes in proteoglycans and collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 46 publications
6
67
0
1
Order By: Relevance
“…Other work has shown increased collagen type I expression and decreased collagen type II expression in canine intervertebral discs subjected to high axial compressive forces in vivo. 64 Similar to the present study, axial compressive loading has been predicted via FEA to translate into both tensile and compressive strains within the three-dimensional structure of the intervertebral disc. 65 Increased passive axial compressive loading levels, therefore, may have helped to drive the development of a more fibrocartilaginous engineered matrix expressing both collagen types I and II.…”
Section: Discussionsupporting
confidence: 59%
“…Other work has shown increased collagen type I expression and decreased collagen type II expression in canine intervertebral discs subjected to high axial compressive forces in vivo. 64 Similar to the present study, axial compressive loading has been predicted via FEA to translate into both tensile and compressive strains within the three-dimensional structure of the intervertebral disc. 65 Increased passive axial compressive loading levels, therefore, may have helped to drive the development of a more fibrocartilaginous engineered matrix expressing both collagen types I and II.…”
Section: Discussionsupporting
confidence: 59%
“…An increase of collagen type I is commonly encountered in degenerating discs in vivo. [47][48][49][50][51] Using immunohistochemistry, Le Maitre et al 52 demonstrated the same pattern of collagen types in an unconstrained culture of human discs. Two independent investigations on rabbit disc stab models also demonstrated a degenerative matrix gene expression in the postinterventional course.…”
Section: Discussionmentioning
confidence: 91%
“…Over the last few decades, several studies have shown that changes in the mechanical environment of the disc can result in remodeling, breakdown, and reorganization of the extracellular matrix [ 1, 7,13,[18][19][20][21][22]29,32,33,35,41,44], leading in some cases to signs of accelerated disc degeneration. Such work forms the *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization and static compression have been shown to induce cell apoptosis and alter mechanical properties (disc thickness, axial compliance and angular laxity), matrix content (proteoglycan and type I and I1 collagen), metalloproteinase activity, and disc cell gene expression (aggrecan and collagen-11) [ 17, [20][21][22][23]29,32]. With respect to the more physiological dynamic loads, Ching et al recently reported that two weeks of dynamic loading of the rat tail intervertebral disc led to a decrease in disc angular compliance, an increase in angular laxity, and a frequency -dependent decrease in disc height [$I.…”
mentioning
confidence: 99%